SWIFT and RTGS operations of Southeast Bank Limited - Biswas, Mehrab Hossain; Brac Business School, Brac University (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.